Exploring the function of relative sentences in New Testament Greek - Toit, Herman C. du (HTS teologiese studies, 2015)
The traditional view of the function of relative sentences in the Greek New Testament differed markedly from that in many modern languages. This view was challenged in the mid-1980s and a number of striking correspondences with a variety of modern (and some classical) languages were pointed out, despite some differences. The purpose of this article is, amongst others, to explore functional aspects of the relative sentence against this background, and to provide further substantiation for the new view and some new perspectives in the light of recent literature. The conclusion is that the view of the functions of the relative sentence, as developed in the mid-1980s, still seems valid. The view is also supported to a large extent by recent literature, especially with respect to the relative sentence’s adjectival use, despite differences relating to nuances and terminology. However, recent New Testament grammars still distinguish so-called ‘conditional’, ‘concessive’, ‘causal’, ‘final’ and ‘resultative’ relative sentences as part of their adverbial use, despite strong evidence to the contrary. The conclusion reached is that relative sentences seem to have the following functions in New Testament Greek, which correspond to their functions in numerous modern languages: (1) Identifying a referent(s) with or without an overt nominal antecedent. (2) Providing background or additional information for a nominal or sentential antecedent in the form of a parenthesis, explanation or concession, or some combination of these. (3) Qualifying a verb with regard to time, location or manner. (4) Functioning as a conjoined sentence.